2018
DOI: 10.1002/bjs.10963
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic outcome following breast-conserving surgery assessed by three evaluation modalities in relation to health-related quality of life

Abstract: There is currently no ideal method for evaluating aesthetic outcome after breast-conserving surgery and adjuvant radiotherapy. These results emphasize the use of patient-related outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Potter et al outlined a core outcome set for breast reconstruction based on Delphi methodology in which 'patient satisfaction with cosmetic outcome' was rated highly amongst medical professionals and patients alike [30]. Patient-Reported Outcome Measures (PROMs) are clearly the most important evaluation of aesthetic outcome but lack objectivity, are affected by the treatment path leading to the final outcome and are consistently discordant from professional assessment, being frequently reported more favourably [9,[31][32][33]. Dahlbäck et al have recently emphasised the importance of PROMs in aesthetic evaluation demonstrating a stronger predictive ability for longer-term health-related quality of life as compared to objective measures or panel assessment [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Potter et al outlined a core outcome set for breast reconstruction based on Delphi methodology in which 'patient satisfaction with cosmetic outcome' was rated highly amongst medical professionals and patients alike [30]. Patient-Reported Outcome Measures (PROMs) are clearly the most important evaluation of aesthetic outcome but lack objectivity, are affected by the treatment path leading to the final outcome and are consistently discordant from professional assessment, being frequently reported more favourably [9,[31][32][33]. Dahlbäck et al have recently emphasised the importance of PROMs in aesthetic evaluation demonstrating a stronger predictive ability for longer-term health-related quality of life as compared to objective measures or panel assessment [9].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is a common and emotive diagnosis with 54,722 new cases diagnosed in the UK in 2017 [1] Twothirds of women managed surgically for breast cancer undergo Breast-Conserving Treatment (BCT). Aesthetic outcome after BCT has a well-documented influence on patients' psychosocial wellbeing and quality of life [2][3][4][5][6][7][8][9][10]. With advancements in treatment and the excellent survival expectations of 90% at 1 year and 80% at 10 years [1], more women are living with the long-term impact of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our findings, future efforts could be undertaken to develop techniques to optimize volumetric and vertical nipple symmetry, and, in turn, patient satisfaction with breast cosmesis, which has been validated as an integral component of long-term quality of life after BCT. 25 , 26 As more women transition to survivorship after being cured of their early stage breast cancer, improving quality of life after cancer treatment becomes paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a study conducted by Dahlback in 2018 concluded that there is no ideal method to evaluate the aesthetic result after surgery, and emphasizes the importance to presenting the results with regard to the patient's health and quality of life [12].…”
Section: Introductionmentioning
confidence: 99%